HENOCH SCHONLEIN PURPURA ASSOCIATED WITH ACUTE POSTSTREPTOCOCCAL GLOMERULONEPHRITIS: A CASE REPORT - Melati, Deborah; Kumara Wati, Ketut Dewi; Putu Nilawati, Gusti Ayu (Medicina; Vol 45 No 2 (2014): Mei 2014)
Acute post-streptococcal glomerulonephritis (APSGN) is one of the most common renal disease resulting from a prior infection with group A â-hemolytic streptococcus (GAS). Henoch Schonlein Purpura (HSP) is a systemic disease with frequent renal involvement, its etiology is still unknown but several infections have been described as trigger includingGAS infection. A 4 year 10 month old Balinese boy presented with full blown acute nephritic syndrome, an elevation in serum creatinine and four fold increase of anti streptolysin-O, also low serum levels of complement C3 with normal C4 confirmed the diagnosis of APSGN. During hospitalization he developed palpable purpura, gastrointestinal symptoms as well as leucytoclastic vasculitis in skin biopsy conclude HSP diagnosis.He was treated with anti-hypertensions and metylprednisolone intravenous. The prognosis of the patient was excellent, he showed normal physical examination with normal complete blood count and urinalysis after 3 months follow up. We conclude that both APSGN and HSP could appear concurrently after GAS infection. [MEDICINA 2014;45:102-7]
Keywords: APSGN, Henoch Schonlein purpura, children, anti streptolysin O